INTERPRETASI MOH. E HASIM DALAM TAFSIR AYAT SUCI LENYEUPANEUN TERHADAP FENOMENA TAKLID - Siti Mursida (Dar el-Ilmi : jurnal studi keagamaan, pendidikan dan humaniora, 2021)
This article discusses the interpretation of Moh. E. Hasim on the phenomenon of taklid that exist in society. At the beginning of the 20th century the phenomena of bid’ah, tahayul, and khurafat were issues that developed at that time. According to Hashim, this phenomenon cannot be separated from the taklid buta that develops in society. Moh. E. Hasim is a very critical modernist figure from the Priangan Sundanese land. This can be seen from many of his interpretations criticizing phenomena that exist in society. Hasim pondered his interpretation in a Sundanese nuanced interpretation entitled the interpretation of the holy verse lenyeupaneun. In his interpretation hasim is very critical. Because according to hasim this causes heresy to the people. The results of this study indicate that the interpretation of hasim does not only include interpreting the meaning of the verse, but also includes criticism of the phenomena that exist in society. This shows that an interpretation will not be separated from the context aspect of the interpreter (horizon teks).